Impact of education and employment status on cognitive and physical disability in multiple sclerosis patients - Silvia Mihaela Patrașc; Emilian Bogdan Ignat; Victor Constantinescu; Alin Ciubotaru; Dragos Andrei Spînu; Ioana Teodora Țaga; Laura Cristina Ivan; Iulian Miron; Daniela Viorelia Matei; Andreea Silvana Szalontay (Balneo and PRM Research Journal, 2023)
Multiple sclerosis (MS) is the most common cause of non-traumatic disability in the young. Socioeconomic status – education and employment - are environmental factors that may influence MS genesis and disease course. We evaluate the impact of education and employment on cognitive and physical disability in a Romanian cohort of people with MS (pwMS). We analyzed data from 111 pwMS in our clinic. Isaacs set test (IST) and EDSS (Expanded Disability Status Scale) were used to evaluate cognition and physical function. Comparison of means and linear regression were used to characterize the relationship between education/employment and cognitive/physical evaluations. Individuals who fit in the ‘high’ education category had higher IST scores as compared to less educated subjects. Employed patients had significantly better IST scores. Linear regression showed that education can predict cognitive (p<.05, B=0.256, CI 0.042-0.469) and physical disability (p<.001, B= -0.43, 95% CI -0.607 to -0.264). EDSS scores were significantly lower in the ‘high education’ and employed groups. While the relationship between these factors is not yet fully comprehended, asking simple questions about one’s socioeconomic status could represent useful tools in evaluating and managing pwMS.